الحماية القانونية للطفل اثناء النزاعات المسلحة - واجعوط, سعاد (University of Eloued جامعة الوادي, 2020)
يتمتع الطفل و هو جنين في بطن امه بمجموعة من الحقوق المدنية والمالية فكرست له ترسانة قانونية تقر له مجموعة من الحقوق التي يحظى بها باعتباره فئة ضعيفة، فسارع المجتمع الدولي لحماية هذه الفئة الضعيفة لضمان استمرار العنصر البشري ، فوضع تعريفا للطفل الذي يحظى بالحماية القانونية الدولية ، فالطفل هو" كل انسان لم يبلغ سن الثامن عشر سنة ،اما في اتفاقيات جنيف فلم تتضمن اي تعريف للطفل الا انها تقرر حماية خاصة للأطفال الاقل من خمسة عشرة سنة ، و في البروتوكول الاضافي الاول لحماية ضحايا النزاعات المسلحة في المادة 77 منه، اثناء النزاعات المسلحة تتمتع بحماية قانونية مزدوجة اثناء النزاعات المسلحة وباليات دولية و وطنية و هيئات انسانية تضمن احترامها و تنفيذها . Child rights Even as a fetus, a child is always protected by a legal arsenal as a fringe that needs its rights to be preserved ,at the same time these rights are always violated during times of war . Knowing that a child is a human being that hasn't reached the age of 18 yet, the Geneva Convention didn't show any interest considering child rights, but still made a special protection system for children who haven't reached the age of 15 , the first additional protocol regarding victims protection within armed conflicts in article 77 , taken by algeria in 05_16_1989 assure the protection of people under the age of 18 and their rights are also preserved in times of peace , and in times of war there should be mecanisms assuring the protection of these rights thus they are legly protected intensively during times of war where international mechanisms and humanitarian institutions work to assure that these rights are being respected.
مجلد11، عدد3
Keywords: الطثل ; حماية الطفل ; اليات الحماية ; حقوق الطفل ; الطفل الضحية; The child ; The protection of child ; The rights of child ; The victim child ; The mechanisms of protection